Investigating the Pollution of the Atmosphere by Motor Transport - D. Yambyshev, Farid; M. Shigabutdinov, Renat (International Journal of Engineering and Technology, 2018)
Environmental pollution is one of the most serious global problems of mankind. Its impact on the public health becomes more acute every year. Ecotoxicants - harmful chemicals that pollute the environment - pose a great danger to humans and animals. Their sources are not only production and energy enterprises, but also motor transport. With the increase in the car fleet, the level of harmful impact on the environment is intensively increasing. For example, if at the beginning of the 1970s, hygienists determined the proportion of pollutants introduced into the atmosphere by road transport on average at 13%, now this level has reached 50% and continues to grow.This paper is devoted to the study of the extent of atmospheric pollution by road transport. Literature sources on this problem have been analyzed and summarized, specific types of pollutants released by the exploited vehicles and the results of their harmful effects on the environment and living organisms have been described. The authors of the paper obtained quantitative data on the average daily and average annual volumes of pollutants emitted into the atmosphere during the operation of vehicles in the city of Kazan.Â
Keywords: environment; motor transport; pollution; ecology; exhaust gases.